Kala : a novel - Walsh, Colin, 1986- (Doubleday, 2023)
"In the seaside village of Kinlough, on Ireland's west coast, three old friends meet for the first time in years. They--Helen, Joe and Mush--were part of an original group of six inseparable teenagers in the summer of 2003, with motherless, reckless Kala Lannan at its white-hot center. But later that year, Kala disappeared without a trace. Now remains have been discovered in the woods--including a skull with a polaroid photo tucked inside--and the town is both aghast and titillated at reopening this old wound. On the eve of this gruesome discovery, Helen had reluctantly returned for her father's wedding, the world-famous musician Joe had come home to dry out and reconnect with something authentic, and Mush had never left, too shattered by the events of that summer to venture beyond the counter of his mother's café. But when two more girls go missing, they are forced confront their own complicity in the events that led to Kala's disappearance. Ultimately, they must do what others should have done before to stop the violent patterns of their town's past repeating themselves once again. In cracklingly vivid prose, Kala brilliantly examines the sometimes brutal costs of belonging, as well as the battle in the human heart between vengeance and forgiveness, despair and redemption"--